El Caso Mundial and El Caso Criminal, new weekly papers in Spain after the disappearance of El Caso (1952-1987) - Rodríguez Cárcela, Rosa (2019)
The paper analyses “El Caso Mundial” and “El Caso Criminal”, both of them event newspapers that emerged in Spain after the disappearance of "El Caso" (Madrid, 1952-1987), and was published by the businessman and journalist Joaquín Abad. Few research has been done on this newspaper that came to fill the gap left by "El Caso", directed by Eugenio Suárez. The sources consulted show that it was really a new journalistic publication, similar to the original one, but different. Therefore, it cannot be considered a second stage. It was printed and distributed from Almería for ten years (1987-1997), although it had a national scope. His informative style, content, directors and the causes that led to its completion on September 24, 1997.